SRSF3 Expression Serves as a Potential Biomarker for Prognostic and Immune Response in Pan-Cancer - Li, Zihua; Huang, Hui; Wu, Xinbo; Yu, Tao; Xiao, Fajiao; Zhou, Haichao; Shang, Anquan; Yang, Yunfeng (Frontiers in Oncology, 2022)
Abstract Background Serine-rich splicing factor3 (SRSF3) plays an essential role in cell proliferation and inducing and maintaining of cancers as a proto-oncogene. However, the mechanisms of SRSF3 in pan-cancers are still unknown. In our study, a visualized the prognostic landscape of SRSF3 in pan-cancer were investigated and visualized and the relationship between SRSF3 expression and immune infiltration was also investigated. Methods The expression pattern and prognostic worth of SRSF3 among pan-cancers were explored through different databases including TCGA and Kaplan-Meier Plotter. Moreover, the survival analysis including Kaplan-Meier method for evaluating between groups was conducted. Further analyses including the correlation between expression SRSF expression and immune infiltration including tumor mutation burden (TMB), microsatellite instability (MSI) were investigated using Spearman test. Results SRSF3 expression was upregulated in pan-cancer tissue compared with normal tissue, which confirmed by immunohistochemistry and its expression indicated poor overall survival as well as death-specific survival. In ACC, KIRP and UCEC cancer, upregulated expression of SRSF3 was associated with worse disease-free interval (DFI), representing a mechanism in promoting progression of tumor. Our results showed that SRSF3 expression was positively correlated immune cell infiltration, TMB, MSI in certain cancer types, indicating SRSF3 expression to potential value of therapy response. Thus, SRSF3 was found to be a possible biomarker for prognostic and therapeutic assessment through bioinformatic analysis. SRSF3 is expressed in various cancers and its high expression correlated to poor survival and disease progression. Conclusions In summary, SRSF3 expression can be considered as a prognostic biomarker in pan-cancer and therapeutic evaluation.